Calypso's spell: accidental near‐fatal thiacloprid intoxication. Issue 10 (5th September 2017) - Zuercher, Patrick; Gerber, Daniel; Schai, Nadia; Nebiker, Matthias; König, Stefan; Schefold, Joerg C.
Key Clinical Message: Acute life‐threatening intoxications with insecticides are rare. We report a case of accidental near‐fatal thiacloprid intoxication with mass spectrometry‐based analytical confirmation. The initial clinical presentation resembled imminent brain death and/or severe postanoxic encephalopathy. Prolonged supportive treatment resulted in full recovery underlining intoxication as an important differential diagnosis in unclear coma. Abstract : Acute life‐threatening intoxications with insecticides are rare. We report a case of accidental near‐fatal thiacloprid intoxication with mass spectrometry‐based analytical confirmation. The initial clinical presentation resembled imminent brain death and/or severe postanoxic encephalopathy. Prolonged supportive treatment resulted in full recovery underlining intoxication as an important differential diagnosis in unclear coma.